SOCIOLOGY OF EDUCATION AND CRITICAL PEDAGOGY - Roger Camdepadrós; Cristina Pulido (Ediciones Universidad de Salamanca, 2009)
One of sociology of education's main task is to identity which theories lead to educational success and which ones lead to educational failure. Only through identifying these elements sociology of education will be socially useful. In this article, we analyze two theoretical perspectives: the one based on the reproduction model, and the dual perspective, related to the contributions of critical pedagogy. It is analyzed which type of practices emerge from the principles of these two theoretical perspectives, and the impact of those practices on social reality.